Response of Soybean Genotypes to Waterlogging - Heru Kuswantoro (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
National demand on soybean can be full filled by extending production area including marginal lands. Tidal swamp is one of marginal lands which potentially can be cultivated for soybean production with the use of tolerant varieties to waterlogging. So far, there are only two varieties that are tolerant to tidal swamp condition. This research was conducted to study the response of soybean genotypes to waterlogging and to provide gene resources in breeding for tidal tolerant variety. The research was conducted from October 2007 to February 2008 in the glasshouse of Indonesian Legume and Tuber Crops Research Institute (ILETRI), Malang. The experimental design was split-plot with two replications; where the main plot was waterlogging treatment and the sub plot was soybean genotype (17 genotypes of ILETRI collection). The results showed that soybean genotypes had different responses to different water treatments, shown on the number of branches and reproductive nodes, the number of filled and unfilled pods, and yield (dry seeds) per plant. Waterlogging inhibited plant growth of all traits. Under waterlogging, the highest number of reproductive nodes and filled pods, and yield per plant was from MLGG 0537 i.e. 12.25, 19.25, and 3.13 g plant-1, respectively.